2018
DOI: 10.1002/jhet.3189
|View full text |Cite
|
Sign up to set email alerts
|

Isatin Derivatives with Potential Antitubercular Activities

Abstract: Tuberculosis is a life‐threatening chronic infectious disease, which primarily affects the lungs but can spread to other vital organs. The re‐emergence and wide spread of new virulent forms of Mycobacterium tuberculosis that are resistant to some or all first and second line antitubercular agents has reached an alarming level in recent decades. Thus, it is imperative to develop more effective agents. Isatin derivatives are endowed with diverse biological properties, therefore thousands of isatin derivatives ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 120 publications
(107 reference statements)
0
34
0
Order By: Relevance
“…[ 1 ] Isatin derivatives have the potential to inhibit many enzymes and receptors such as acetylcholinesterase, [ 2 ] butyrylcholinesterase, [ 3 ] carbonic anhydrase, [ 4 ] DNA gyrase, [ 5 ] histone deacetylase, [ 6 ] reverse transcriptase, [ 7 ] serine proteases, [ 8 ] tyrosine kinase, [ 9 ] and tubulin, [ 10 ] so this kind of compound possesses a variety of pharmacological properties. [ 11–16 ] Moreover, various isatin‐containing derivatives such as hesperadin, intedanib, nintedanib, semaxanib, and sunitinib have already been used in the clinical practice, [ 17,18 ] revealing their potential in the development of novel drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Isatin derivatives have the potential to inhibit many enzymes and receptors such as acetylcholinesterase, [ 2 ] butyrylcholinesterase, [ 3 ] carbonic anhydrase, [ 4 ] DNA gyrase, [ 5 ] histone deacetylase, [ 6 ] reverse transcriptase, [ 7 ] serine proteases, [ 8 ] tyrosine kinase, [ 9 ] and tubulin, [ 10 ] so this kind of compound possesses a variety of pharmacological properties. [ 11–16 ] Moreover, various isatin‐containing derivatives such as hesperadin, intedanib, nintedanib, semaxanib, and sunitinib have already been used in the clinical practice, [ 17,18 ] revealing their potential in the development of novel drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the bis‐nuclear compounds have been attracted great interests in the drug development since they usually exhibited some unique properties such as enhanced biological activities compared with the corresponding mono‐nuclear analogs . Bis‐isatin derivatives demonstrated promising anti‐cancer, anti‐viral and anti‐TB activities,, and the structure‐activity relationship (SAR) revealed that the linker between the two isatin moieties played a pivotal role in exert their biological activities . Diethylene glycol fragment has the potential to exert diverse noncovalent interactions, which may facilitate the bind with active site, and some diethylene glycol tethered derivatives possess considerable biological activities ,.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of isatin in to C‐7 position of fluoroquinolones could improve the lipophilic character and consequently boost up the anti‐TB activity , and some CPFX–isatin hybrids exhibited excellent anti‐TB activities . The structure–activity relationship suggested that the linker between the fluoroquinolones and isatin played a pivotal role in the exertion of the anti‐TB activity and the linker that could exert noncovalent bind interactions benefited the activity .…”
Section: Introductionmentioning
confidence: 99%